Senior secondary school students' perception of class size influence on chemistry learning in Etche Local Government Area, Rivers State - Nduudee, Joy Nenalebari; Shedrack, Tamunoiyowuna (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2024)
This research explores students' perception of how class size influences the learning of chemistry at the senior secondary school level in Etche LGA, Rivers State, Nigeria. Employing a descriptive survey design, the study surveyed 250 students from 10 secondary schools out of a total population of 1,950 students across thirteen schools in Etche LGA. Data collection was conducted using the "Influence of Class Size on Chemistry Students' Learning (ICSCSL)" questionnaire, which demonstrated high reliability with a Cronbach Alpha coefficient of 0.85. Mean and standard deviation were utilized to address research questions. Findings revealed that respondents generally concurred on the influence of class size on teachers' ability to supervise student notes, guide experiments, and support students with learning disabilities. Large class sizes were associated with challenges such as tedious lessons, student anxiety, limited teacher accessibility, and difficulties in managing student behaviour. The study underscores the importance of class size in shaping the quality of chemistry education delivery, advocating for strategies to tackle challenges posed by large class sizes and leverage the benefits of smaller class settings for an enhanced learning experience. The findings support the recommendation in the National Policy on Education to reduce the number of pupils accepted to each class.